Electrophysiological assessment of a peptide amphiphile nanofiber nerve graft for facial nerve repair. (16th May 2018) - Greene, Jacqueline J.; McClendon, Mark T.; Stephanopoulos, Nicholas; Álvarez, Zaida; Stupp, Samuel I.; Richter, Claus‐Peter
Abstract: Facial nerve injury can cause severe long‐term physical and psychological morbidity. There are limited repair options for an acutely transected facial nerve not amenable to primary neurorrhaphy. We hypothesize that a peptide amphiphile nanofiber neurograft may provide the nanostructure necessary to guide organized neural regeneration. Five experimental groups were compared, animals with (1) an intact nerve, (2) following resection of a nerve segment, and following resection and immediate repair with either a (3) autograft (using the resected nerve segment), (4) neurograft, or (5) empty conduit. The buccal branch of the rat facial nerve was directly stimulated with charge balanced biphasic electrical current pulses at different current amplitudes whereas nerve compound action potentials (nCAPs) and electromygraphic responses were recorded. After 8 weeks, the proximal buccal branch was surgically reexposed and electrically evoked nCAPs were recorded for groups 1–5. As expected, the intact nerves required significantly lower current amplitudes to evoke an nCAP than those repaired with the neurograft and autograft nerves. For other electrophysiologic parameters such as latency and maximum nCAP, there was no significant difference between the intact, autograft, and neurograft groups. The resected group had variable responses to electrical stimulation, and the empty tube group was electrically silent. Immunohistochemical analysis and transmission electron microscopy confirmed myelinated neural regeneration. This study demonstrates that the neuroregenerative capability of peptide amphiphile nanofiber neurografts is similar to the current clinical gold standard method of repair and holds potential as an off‐the‐shelf solution for facial reanimation and potentially peripheral nerve repair.